2021
DOI: 10.7554/elife.70676
|View full text |Cite
|
Sign up to set email alerts
|

The roles of history, chance, and natural selection in the evolution of antibiotic resistance

Abstract: History, chance, and selection are the fundamental factors that drive and constrain evolution. We designed evolution experiments to disentangle and quantify effects of these forces on the evolution of antibiotic resistance. Previously we showed that selection of the pathogen Acinetobacter baumannii in both structured and unstructured environments containing the antibiotic ciprofloxacin produced distinct genotypes and phenotypes, with lower resistance in biofilms as well as collateral sensitivity to b-lactam dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 78 publications
0
21
0
1
Order By: Relevance
“…Experimental evolution has been an essential tool to address these questions and to unravel the interaction between selection, chance, and historical contingency in microbial populations ( Weinreich et al 2006 ; Jansen et al 2013 ; Blount et al 2018 ; Roemhild et al 2018 ; Santos-Lopez et al 2021 ). By combining experimental microbiology with whole-genome sequencing, previous studies have been able to follow evolutionary trajectories towards resistance and studied the accumulation of mutations in different ecological contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evolution has been an essential tool to address these questions and to unravel the interaction between selection, chance, and historical contingency in microbial populations ( Weinreich et al 2006 ; Jansen et al 2013 ; Blount et al 2018 ; Roemhild et al 2018 ; Santos-Lopez et al 2021 ). By combining experimental microbiology with whole-genome sequencing, previous studies have been able to follow evolutionary trajectories towards resistance and studied the accumulation of mutations in different ecological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that, as selection increases, the benefit associated with drug-resistance mutations is enhanced, thus increasing mutant frequency in the population and reducing overall genetic diversity. Consequently, strong selective pressures often display similar phenotypic trajectories towards resistance ( Toprak et al 2012 ) and are known to mitigate the effect of historical contingencies ( Pennings 2012 ; Santos-Lopez et al 2021 ). Population bottlenecks are also major determinants of the repeatability of adaptation as they affect genetic drift ( De Visser and Krug 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the effect we observed was strong when the phage selection event was recent but was no longer detectable after populations had spent an extended period of time in the same environment. Thus, recent historical differences appear to be more important than distant historical differences in shaping subsequent evolution ( Travisano et al 1995 ; Yen and Papin 2017 ; Santos-Lopez et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that multiple genes of various effects determine antibiotic resistance in planktonic bacteria (Petchiappan and Chatterji, 2017;Apjok et al, 2019;Igler et al, 2021). Similarly, multiple mutations were recently implicated in biofilm recalcitrance (Santos-Lopez et al, 2019;Santos-Lopez and Cooper, 2021). Evolutionary experiments have shown that when biofilm and planktonic bacteria are exposed to increasing concentrations of antibiotics, the biofilm populations harbor even higher genetic diversity than planktonic populations that experienced the same treatment (Ahmed et al, 2018(Ahmed et al, , 2020Santos-Lopez et al, 2019;Santos-Lopez and Cooper, 2021).…”
Section: Introductionmentioning
confidence: 99%